Mainstreaming HIV and AIDS into Livelihoods and Food Security Programs: The Experience of CARE Malawi - Drimie, Scott; Mullins, Dan (International Food Policy Research Institute, 2006)
It is now well recognized that household food insecurity in Southern Africa can be properly understood and addressed only if HIV/AIDS is factored into the analysis. Analysis of linkages between food security and HIV/AIDS show that the relationships work in both directions and are systemic, affecting all aspects of livelihoods (Haddad and Gillespie 2001). Effective analysis and action to influence the causes and outcomes of HIV/AIDS requires a contextual understanding of livelihoods (SADC FANR Vulnerability Assessment Committee 2003).